FACTORS ASSOCIATED WITH HYPERTENSION AMONG HIV POSITIVE PATIENTS USING ANTIRETROVIRAL THERAPY AT DISTRICT HOSPITAL, RWANDA - Sendegeya Jean Pierre, Dr. Okova Rosemary , Eric Kinara (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Hypertension is a public health problem globally, largely not diagnosed at an early stage, during the year 2019 this disease accounted for 17.9 million (32%) death globally. Worldwide the number people living with HIV are 37.6 million. The principal aim of this study was to find out the associated factors of hypertension in HIV-positive patients using ART and thus was guided by the following specific objectives: To determine the prevalence and factors associated with hypertension at Kigeme District Hospital. The findings from this study will be useful in early diagnoses of hypertension in HIV-positive patients using antiretroviral drugs. Methods and Materials: A cross-section study design was used at Kigeme District Hospital in HIV service. A total of 207 study participants were selected with simple random sampling respecting inclusion and exclusion criteria. Data on social-demographic, hypertension, clinical and lifestyle factors were collected using standardized questionnaire. Data were analyzed through SPSS V21 where binary and Multivariate logistic regression model was used to determine the factors association with hypertension in HIV-positive patients using ART. Results: Results are resented in odds ratio with its corresponding confidence interval. Mount Kenya University ethical committee and Kigeme District Hospital provided the ethical clearance for an approval. A total of 207 HIV-positive patients using ART attending Kigeme District Hospital from Southern Province of Rwanda were recruited in this study where mean age of participants was 52.76 years and majority of participants were female (61.8%). 87% of study participants had been on antiretroviral medications for < 10 years. The prevalence of hypertension was 15.9%. Being male was associated with higher odds of hypertension (AoR: 5.09, 95%CI 1.3-21.2, p-value: 0.025). Being hypertensive before diagnosis of HIV was associated with this health event with AoR: 0.1, 95%CI: 0.021-0.466,P=0.003. Diabetes mellitus has a negative association ( AoR: O.O62, 95%CI:0.005-0.7,p=0.027). In addition overweight or obese is statically significant associated of hypertension (AoR: 34.5, 95%CI: 8.9-134.2, p-value: 0.0001). Age, occupation, level of education, CKD, physical exercises, alcohol consumption, smoking and HIV-related health factors are not significantly associated with hypertension. Conclusion: In conclusion hypertension is common for patient using ART at Kigeme District Hospital where the findings indicated that 15.9% of these people are hypertensive .The factors like being male ,diabetes mellitus, being overweight or obese , history of hypertension before HIV are likely associated with the increase of hypertension. This research study recommends that there be early detection of hypertension and further researches to find out the causality of this health condition in HIV-positive patients using ART.